Landscape planning rules in designing new cities in Iran - Lesan, Maryam; Ghazanfari, Parvane (2008)
New cities differ from more elder cities which are built gradually overtime due to several reasons. The new cities don’t follow any program and are built on unused areas and through natural environments .their construction happens due to increasing demands through awareness and thoughts, in other words newly developing cities are based upon previously made plans in hope to achieve a successful community for the residency of social groups. Unfortunately, in Iran as a developing country the fact that the building of these new cities have started twenty years ago, statistical analysis show they haven’t reached their goals. Despite work being commenced in new cities here most remain uncompleted and the respected population has not yet been achieved and In the opinions of most experts many problems exist in the construction of these cities.